Effects of sudden commencement on the ionosphere: PFISR observations and global MHD simulation. Issue 7 (14th April 2017) - Zou, Shasha; Ozturk, Dogacan; Varney, Roger; Reimer, Ashton
Abstract: Sudden commencement (SC) induced by solar wind pressure enhancement can produce significant global impact on the coupled magnetosphere‐ionosphere (MI) system, and its effects have been studied extensively using ground magnetometers and coherent scatter radars. However, very limited observations have been reported about the effects of SC on the ionospheric plasma. Here we report detailed Poker Flat Incoherent Scatter Radar (PFISR) observations of the ionospheric response to SC during the 17 March 2015 storm. PFISR observed lifting of the F region ionosphere, transient field‐aligned ion upflow, prompt but short‐lived ion temperature increase, subsequent F region density decrease, and persistent electron temperature increase. A global magnetohydrodynamic (MHD) simulation has been carried out to characterize the SC‐induced current, convection, and magnetic perturbations. Simulated magnetic perturbations at Poker Flat show a satisfactory agreement with observations. The simulation provides a global context for linking localized PFISR observations to large‐scale dynamic processes in the MI system. Key Points: PFISR‐observed ionospheric plasma responses to field‐aligned currents and ionospheric convection vortices formed during sudden commencement Responses include F region plasma lifting, field‐aligned ion upflow, density decrease, short‐lived T i increase and long‐lasting T e increase Global MHD simulation reproduced the magnetic perturbation on the ground and revealed SC‐related FACs and convection evolutions